Research of Calculation Method of Contact Stress of Non-orthogonal Modified Face-gear Drive with Helical Pinion - Yang Zhuxi; Wu Yuanhang; Tang Jinyuan (Jixie chuandong)
Non-orthogonal modified face-gear drive is a kind of cross-shaft transmission mode with universal application. At present， there is no analytical formula for contact stress， only finite element software can be used to calculate the contact stress. The calculation method and formula of the contact stress are given in this study. Firstly， based on the principle of surface meshing transmission， the tooth surface equation of non-orthogonal modified face-gear drive with helical pinion is derived. Secondly， the contact analysis coordinate system with installation error is established， and the contact point and its curvature calculation equation are obtained by the tooth contact analysis (TCA) theory. Finally， the general form of the contact stress analytical formula is derived according to the Hertz contact theory. The contact stress calculation formula can calculate the contact stress of various types of face gears， such as orthogonal and non-orthogonal， modified and unmodified， spur and helical teeth， and quickly calculate the corresponding contact stress by programming. Taking a certain design parameter of the face-gear drive as an example， the contact stress calculation formula is used to calculate the contact stress， and the Abaqus finite element software is used to calculate the tooth surface contact stress of face gear， and then the tooth surface contact stress value of face gear is extracted in Abaqus. The results of analytical calculations are compared with the finite element， the error is about 5.23%. The results show that the calculation method of contact stress of helical face gear tooth surface is correct and feasible.